'I look at him and he looks at me': Stein's phenomenological analysis of love. Issue 1 (15th March 2017) - Wulf, Claudia Mariéle
ABSTRACT: The Jewish-Catholic philosopher and Carmelite Edith Stein (1891–1942) offers a rich notion of love, based on an original phenomenology, which resulted from an active engagement with her teachers Edmund Husserl and Max Scheler, and was later enriched and deepened by incorporating religious philosophical and theological ideas. In order to locate Stein's original thinking, the essay will first introduce the two thinkers by whom she was most clearly influenced, and show how Stein contrasted the 'nothing', as it is presented in Husserl's other pupil Martin Heidegger's existentialist analysis, with the fullness of being to which the human person aspires, and which is given through love (1). Her phenomenological thinking, based on the intersubjective approach to its object, ultimately leads Stein to a triple philosophical statement about love: Love is a principle of being, a principle of knowledge and a principle of relationship (2). The passage through theology verifies what has been said philosophically about its relationship to God, in whom love ultimately finds its completion (3). The three basic principles of love complement and correct each other, to the point not only of issuing in an analysis of the phenomenon 'love' but of also opening up an ethics of love (4).